Upaya UPT Rehabilitasi Sosial Bina Laras Pasuruan Dalam Meningkatkan Kemandirian Klien Eks Psikotik - Nur Cholifah, Siti; Sidiq, Mahfudz; Santoso, Budhy; Nugroho Puspito, Agung (Multidisciplinary Journal, 2023)
An ex-psychotic sufferer is someone who has experienced mental disorders and is declared medically cured by a Mental Hospital who has obstacles in incommunicating, socializing in the community, and has low independence. This is what makes ex-psychotic sufferers unable to carry out their social functions in the community properly and require various efforts to increase their independence through social rehabilitation activity programs. The purpose of this study is to know, analyze and describe the efforts made by UPT Social Rehabilitation Bina Laras Pasuruan in increasing the independence of ex-psychotic clients. The type of research used is descriptive with a qualitative approach. Determination of the location of this study using purposive area. The informant determination technique uses purposive sampling. Data analysis techniques begin with data collection, data reduction, data presentation, conclusion drawing and verification. Data validity techniques use triangulation of sources and methods. The results showed that there were several efforts made by UPT, namely through guidance or advanced medical therapy, physical guidance, social guidance, religious mental guidance, and skill or vocational guidance.